2018
DOI: 10.1242/dev.163469
|View full text |Cite
|
Sign up to set email alerts
|

Stratum recruits Rab8 at Golgi exit sites to regulate the basolateral sorting of Notch and Sanpodo

Abstract: In , the sensory organ precursor (SOP or pI cell) divides asymmetrically to give birth to daughter cells, the fates of which are governed by the differential activation of the Notch pathway. Proteolytic activation of Notch induced by ligand is based on the correct polarized sorting and localization of the Notch ligand Delta, the Notch receptor and its trafficking partner Sanpodo (Spdo). Here, we have identified Stratum (Strat), a presumptive guanine nucleotide exchange factor for Rab GTPases, as a regulator of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 61 publications
5
36
0
Order By: Relevance
“…Therefore Su(H) can be used as a read-out of cell fate transformations to monitor the effect of individual or simultaneous impairment of Strat and AP-1 ( Fig.1). In agreement with previous studies, mild Notch GOF phenotypes revealed by an excess of Su(H) positive socket cells were observed in 6,7% and 7,5% of SO mutant for strat or depleted of AP-1, respectively (Bellec et al, 2018;Benhra et al, 2011). However simultaneous loss of AP-1 and Strat led to a much stronger Notch GOF phenotype (49% of transformed SOs, Fig.1B-C).…”
Section: Simultaneous Loss Of Ap-1 and Strat Causes A Penetrant Notchsupporting
confidence: 92%
See 4 more Smart Citations
“…Therefore Su(H) can be used as a read-out of cell fate transformations to monitor the effect of individual or simultaneous impairment of Strat and AP-1 ( Fig.1). In agreement with previous studies, mild Notch GOF phenotypes revealed by an excess of Su(H) positive socket cells were observed in 6,7% and 7,5% of SO mutant for strat or depleted of AP-1, respectively (Bellec et al, 2018;Benhra et al, 2011). However simultaneous loss of AP-1 and Strat led to a much stronger Notch GOF phenotype (49% of transformed SOs, Fig.1B-C).…”
Section: Simultaneous Loss Of Ap-1 and Strat Causes A Penetrant Notchsupporting
confidence: 92%
“…Indeed, we found that Numb and Neur localize asymmetrically during prometaphase in absence of Strat and AP-1 ( Fig.2A-B). Liveimaging of Numb::GFP crispr (Bellec et al, 2018) revealed that Numb is unequally partitioned in the anterior SOP daughter cell, in a similar manner as in the control situation ( Fig.2C-D).…”
Section: Despite These Cuticle Defects the Localization Of The Junctmentioning
confidence: 53%
See 3 more Smart Citations